A small free kiss in the dark - Millard, Glenda (Holiday House, 2010)
Skip, an eleven-year-old runaway, becomes friends with Billy, a homeless man, and together they flee a war-torn Australian city with six-year-old Max and camp out at a seaside amusement park, where they are joined by Tia, a fifteen-year-old ballerina, and her baby.